2017
DOI: 10.2967/jnumed.117.195685
|View full text |Cite
|
Sign up to set email alerts
|

Iodinated Contrast Agents Perturb Iodide Uptake by the Thyroid Independently of Free Iodide

Abstract: Perturbation of thyroid iodide uptake is a well-documented side effect of the use of iodinated contrast media (ICM) administered intravenously. This side effect is thought to be mediated by free iodide in ICM formulations, but this hypothesis has never been formally proven. The aim of the present study was to assess the validity of this hypothesis. We used mass spectrometry analysis to quantify free-iodide contamination in ICM. Established cell lines expressing the Na/I symporter (NIS) were used to quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…These results indicated that UI concentration within normal range cannot guarantee the absence of interference from ICM in terms of clinical outcome. This was in accordance with the theory proposed by Vassaux et al (14) in in vitro studies as mentioned previously. Therefore, our study demonstrated in a clinical practice setting that it might be not suitable for using a "normal UI concentration" to decide the initiation of RAI therapy if the patients had received preoperative ICM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results indicated that UI concentration within normal range cannot guarantee the absence of interference from ICM in terms of clinical outcome. This was in accordance with the theory proposed by Vassaux et al (14) in in vitro studies as mentioned previously. Therefore, our study demonstrated in a clinical practice setting that it might be not suitable for using a "normal UI concentration" to decide the initiation of RAI therapy if the patients had received preoperative ICM.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, in a recent study, Vassaux et al suggested that independent of free iodide, the ICM itself could directly reduce thyroid iodide uptake by decreasing NIS expression in thyroid cells. Besides, they found that ICM induces thyroid stunning to a greater and longer-lasting degree than free iodide found in ICM could explain (14). Thus, the influence of the use of ICM might have been stronger and more enduring than we previously thought.…”
Section: Discussionmentioning
confidence: 72%
“…BHK21, MCF7, MDA-MB231, HeLa and DDIT4 +/+ and -/- MEF cells were obtained and cultured as previously described [ 50 , 58 62 ]. Fluorescence imaging and Western blots were performed as previously described [ 63 , 64 ]. Quantification of the number of fluorescent cells as well as the intensity of fluorescence was performed using the CellQuant program (available at: http://biophytiro.unice.fr/cellQuant/index_html ).…”
Section: Methodsmentioning
confidence: 99%
“…37 Immuno-Fluorescence Experiments NIS-B16F10 cells plated in 24-well format were allowed to grow 24 hrs at 37°C and 5 % CO 2 before being fixed (2% PFA) and permeabilized (0.1% triton). After a blockade step (BSA 1%), immunofluorescence labelling was performed according to 38 using NIS Ab25, anti-mNIS is an affinity purified rabbit polyclonal antibody as previously described. 39…”
Section: Cell Culturementioning
confidence: 99%
“…Iodide uptake in whole cells was performed according to 38 with 30 μM NaI and 125 I. Measurements were made after 1 hr in the presence or the absence of 100 mM perchlorate, a NIS inhibitor. The radioactivity was measured using a gamma counter (Packard Cobra).…”
Section: Iodide Uptakementioning
confidence: 99%